CURRENT TRENDS IN THE DEVELOPMENT OF SERVICES IN UKRAINE - ANHELKO, Iryna; SAMOTIY, Nataliia; LEKH, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the features and trends in the development of services in Ukraine. The structure of volumes of sold services in the context of economic activities and individual consumer groups is analyzed. It is determined that despite the socio-economic instability in the country, the level of services in Ukraine remains quite high and dynamically positive. According to the analysis of the structure of the volume of sold services by spheres of economic activity, it was found that the largest share in the total volume of sold services falls on transport services, warehousing, postal and courier activities. At the same time, it was found that out of the total volume of services provided in Ukraine, only 20% are sold to the population. It is determined that the contribution of the services sector to the formation of the country’s GDP is quite significant. The largest share in the structure of GDP is occupied by wholesale and retail trade, repair of motor vehicles and motorcycles. It is proved that maintaining the share of services at a fairly high level in the structure of GDP in recent years is primarily a consequence of its «penetration» into virtually all economic activities. It is emphasized that in the modern economic space, services are provided not only by traditional service, but also by industrial entities. However, it is determined that the production process itself is impossible without the involvement of additional resources in the form of services, including design, research, preparation of technical documentation and more. It is established that in modern conditions the service sector in Ukraine, as well as the economy as a whole, suffers significant losses. It is generalized that in order to support the development of components of the service sector, which today suffer significant losses, it is necessary to solve a set of complex tasks that play a significant role and are necessary to minimize the economic consequences of the war in Ukraine. The implementation of the proposed measures will have a positive impact on the socio-economic development of the country.